Daya Dukung dan Limbah Pertanian sebagai Sumber Pakan Ternak Ruminansia di Kecamatan Cicalengka Kabupaten Bandung - Dhiaksi, Feren Lefita Rahma; Saefulhadjar, Deny; Mansyur, Mansyur (Unpad Press, 2025)
ABSTRACTThe development of livestock in an area must have a measurement of the potential of the area to be developed better, because livestock production will often depend on the carrying capacity of feed. Data collection using secondary data from which mostly comes from the Agricultural Education Agency (BPP) accompanied by data from the Forestry Service Branch of Region V using the latest available data. Data analysis using descriptive analysis, the technique used using the main calculation from Nell and Rollinson in 1974 with data on land area and harvest area. Analyzing the carrying capacity of feed, the carrying capacity of agricultural waste products, the number of livestock converted to animal units (AU), the carrying capacity index, livestock capacity, and the increase in livestock population. The results showed that feed from agricultural waste had the largest amount compared to feed from green fodder. The carrying capacity of feed which has a value of 4,222.87 AU and the carrying capacity of livestock feed from agricultural waste which has a value of DM 4,127.02 AU, CP 4,820.31 AU, and TDN and 3,588.04 AU. The carrying capacity of agricultural waste has a smaller TDN value than DM and CP resulting in low feed efficiency. Based on the carrying capacity index status of 41.02, it shows a safe status, which means that the feed available in Cicalengka District can meet livestock needs.